Incidence, Predictors, and Clinical Impact of Early Prasugrel Cessation in Patients With ST‐Elevation Myocardial Infarction. Issue 8 (13th April 2018) - Koskinas, Konstantinos C.; Zanchin, Thomas; Klingenberg, Roland; Gencer, Baris; Temperli, Fabrice; Baumbach, Andreas; Roffi, Marco; Moschovitis, Aris; Muller, Oliver; Tüller, David; Stortecky, Stefan; Mach, Francois; et al.
Abstract : Background: Early withdrawal of recommended antiplatelet treatment with clopidogrel adversely affects prognosis following percutaneous coronary interventions. Optimal antiplatelet treatment is essential following ST‐segment elevation myocardial infarction (STEMI) given the increased risk of thrombotic complications. This study assessed the frequency, predictors, and clinical impact of early prasugrel cessation in patients with STEMI undergoing primary percutaneous coronary interventions. Methods and Results: We pooled patients with STEMI discharged on prasugrel in 2 prospective registries (Bern PCI Registry [NCT02241291] and SPUM‐ACS (Inflammation and Acute Coronary Syndromes) [NCT01000701]) and 1 STEMI trial (COMFORTABLE‐AMI (Comparison of Biomatrix Versus Gazelle in ST‐Elevation Myocardial Infarction) [NCT00962416]). Prasugrel treatment status at 1 year was categorized as no cessation; crossover to another P2Y12 ‐inhibitor; physician‐recommended discontinuation; and disruption because of bleeding, side effects, or patient noncompliance. In time‐dependent analyses, we assessed the impact of prasugrel cessation on the primary end point, a composite of cardiac death, myocardial infarction, and stroke. Of all 1830 included patients (17% women, mean age 59 years), 83% were treated with new‐generation drug‐eluting stents. At 1 year, any prasugrel cessation had occurred in 13.8% of patients including crossover (7.2%), discontinuation (3.7%), and disruption (2.9%). Independent predictors of any prasugrel cessation included female sex, age, and history of cerebrovascular event. The primary end point occurred in 5.2% of patients and was more frequent following disruption (hazard ratio 3.04, 95% confidence interval, 1.34–6.91; P =0.008), without significant impact of crossover or discontinuation. Consistent findings were observed for all‐cause death, myocardial infarction, and stent thrombosis following prasugrel disruption. Conclusions: In this contemporary study of patients with STEMI, early prasugrel cessation was not uncommon and primarily involved change to another P2Y12 ‐inhibitor. Disruption was the only type of early prasugrel cessation associated with statistically significant excess in ischemic risk within 1 year following primary percutaneous coronary interventions.